When will Consciousness emerge? - Imants Vilks (Bulletin of Electrical Engineering and Informatics, 2013)
The article is a short rewiev about one particular but important and essential question in the field of AI: the consciousness. The main idea is to cast away non-scientific pronouncements about mystics and impossibility in the field. To clear up the basic notions (emergence) and define the main theme - consciousness. The article proposes temporary definition of consciousness, consciousness emergence conditions and how to recognize and test the consciousness.